Regulatory reform and labour earnings in Portuguese banking - Monteiro, Natália (2009)
This study examines changes in union contracts and wage structure during and after the introduction of regulatory reforms (deregulation and privatisation) in the Portuguese banking sector. The main finding is that, despite a relative wage erosion detected in the contract data, banking workers were able to enjoy an increasing wage premium in the period 1985-2000, probably refflecting the increasing profitability of the industry and the rise in labour productivity. The evidence also shows that some speciffic groups benefited relatively more than others: the least skilled and educated workforce and male workers gained more from the regulatory reforms. However, this unequal sharing of the wage premium did not raise wage inequality across ownership groups in the industry.